INCLUSIVE SPACE IN THE LITERATURE FOR CHILDREN (On the base of the tale “Non-jumping Bunny and his Brave Mother” by Oksana Drachkovska) - Derkachova , Olga; Ushnevych, Solomiya; Tytun, Oksana (Mountain School of Ukrainian Carpaty, 2020)
The article deals with research on inclusive space in children’s inclusive literature. Today creating a Ukrainian inclusive educational environment is an important issue. However, a friendly space is as important as a friendly society. Inclusive literature, in particular literature for children, contributes to creating a friendly community. The peculiarities of the Ukrainian inclusive environment in the literary context are considered on the example of the book for children by Oksana Drachkovska “Non-jumping Bunny and his Brave Mother”. The aim of the writer and, accordingly, Mother Zaichykha from the given tale is to solve problems when creating such an environment. It is the environment where all children study together according to general education programs. The author creates an outstanding example of inclusive space where it is comfortable and good for everyone.